1993
DOI: 10.1006/viro.1993.1360
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of the Surface Protein of Human Coronavirus OC43

Abstract: The two surface glycoproteins S and HE of human coronavirus OC43 (HCV-OC43) were isolated from the viral membrane and purified. Only the S protein was able to agglutinate chicken erythrocytes, indicating that this viral protein is the major hemagglutinin of HCV-OC43. The receptor determinant recognized by this virus on the surface of erythrocytes is N-acetyl-9-O-acetylneuraminic acid (Neu5,9Ac2) which is also used by bovine coronavirus for attachment to cells. By analyzing erythrocytes containing different amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
98
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 0 publications
7
98
1
Order By: Relevance
“…Previous virus infection studies have shown that Neu5,9Ac2 can function as a receptor or co-receptor for BCoV (4,5). However, it is not clear whether any other type of sugar may also have high affinity for BCoV NTD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous virus infection studies have shown that Neu5,9Ac2 can function as a receptor or co-receptor for BCoV (4,5). However, it is not clear whether any other type of sugar may also have high affinity for BCoV NTD.…”
Section: Resultsmentioning
confidence: 99%
“…BCoV and HCoV-OC43 recognize a sugar moiety, 5-N-acetyl-9-O-acetylneuraminic acid (Neu5,9Ac2), on cell-surface glycoproteins or glycolipids (4,5). In contrast, MHV does not use sugar as a receptor (6).…”
mentioning
confidence: 99%
“…Furthermore, for some lectins, the glycerol-like side chain of sialic acid is essential for recognition and 9-O-acetylation of this side chain can block the interaction (11, 18 -20, 22, 26, 30, 31). In other instances, 9-O-acetylation is required for recognition (11,(32)(33)(34)(35)(36)(37). Here we have evaluated the importance of the N-acyl-and 9-O-acetyl groups of sialic acid for recognition by SNA and MAH.…”
mentioning
confidence: 96%
“…By virtue of forming the "canopy" of the glycocalyx, Sias are recognized and used as attachment sites by a large number and wide variety of microbial pathogens and their toxins. Many Sia-binding proteins of different pathogens have been well characterized and generally show a high degree of specificity for different types of Sias and/or their linkage to the underlying glycan chain (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%